Medium control envelope surface to improve the thermal comfort of a house in Huaraz - Corrales Picardo, Miguel Ronald (2021)
The work determined the medium control envelope surface to improve the thermal comfort of a house in the city of Huaraz - Peru, for which, two houses with the same design, but with different envelopes were compared, one existing with a typical minimum control construction and the other with an improved medium control envelope, which takes advantage of passive solar energy. The thermal calculation was performed by analyzing heat gains and heat losses. In conclusion, the proposed envelope surface substantially improved the thermal comfort of a dwelling in Huaraz; predicting that, with an overall thermal transmittance coefficient of 1.05 W/m2 °C, with the support of passive solar heating, an indoor temperature of 21 ± 1°C is achieved, where more than 90% of the occupants are satisfied. Keywords: Thermal envelope; average control; solar radiation.